THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASE DECISION ON GAME STORY BOARD GAME & CAFE WITH BUYING INTEREST AS AN INTERVENING VARIABLE - Perwiranegara, Bintang (Universitas Nusa Cendana, 2025)
This research aims to test, firstly, the direct relationship between product quality and buying interest; secondly, the direct relationship between service quality and buying interest; thirdly, the direct relationship between product quality and purchasing decisions; fourthly, the direct relationship between service quality and purchasing decisions; and fifth, the relationship between buying interest and purchasing decisions. Then the sixth is to test whether buying interest can mediate product quality on purchase decisions, and the seventh is whether buying interest can mediate service quality on purchase decisions. This research uses descriptive quantitative methods to analyze and describe the data. This research took samples from the Game Story Board Game & Café in Kalasan District, Sleman Regency, D.I.Y. Province. The sampling method is non-probability using a purposive sampling technique. Data was collected through an explanatory survey using QR code questionnaires sent via WhatsApp social media. There were 115 questionnaires, and the data was analyzed using multiple linear regression using SPSS version 23. The results of this research show that the first result, namely the product quality variable, has a direct effect on buying interest; the second result, namely the service quality variable, has a direct impact on buying interest; the third result, namely product quality, has a direct effect on purchase decisions; and the fourth result, namely service quality, has a direct impact on purchase decisions. The fifth result indicates that buying interest directly influences purchase decisions. Meanwhile, the sixth result is that intervening buying interest can only mediate product quality in purchase decisions, and the seventh result is that buying interest cannot mediate service quality in purchase decisions. Keywords: Product Quality; Service Quality; Buying Interest; Purchase Decision